2020
DOI: 10.31557/apjcp.2020.21.8.2403
|View full text |Cite
|
Sign up to set email alerts
|

WT1 Clone 6F-H2 Cytoplasmic Expression Differentiates Astrocytic Tumors from Astrogliosis and Associates with Tumor Grade, Histopathology, IDH1 Status, Apoptotic and Proliferative Indices: A Tissue Microarray Study

Abstract: Objectives: This tissue microarray (TMA) immunohistochemical (IHC) study elucidates the role of Wilms' tumor 1 protein (WT1) in diagnosis and prognostication of astrocytic tumors. Methods: IHC was applied to 75 astrocytic lesions (18 astrogliosis and 57 astrocytic tumors) using antibodies directed against WT1 clone 6F-H2, isocitrate dehydrogenase 1(IDH1), Bcl2 and Ki67. WT1 IHC staining was evaluated and scored blindly by 2 pathologists. Bcl2 and Ki67 scores and labelling indices were assessed and IDH1 status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In the current investigation, WT1 expression was identified in each of the 54 astrocytomas (100%) that were examined. Similar findings from earlier trials with positive ranging between 80.9% and 100% 25,26 have been reported.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current investigation, WT1 expression was identified in each of the 54 astrocytomas (100%) that were examined. Similar findings from earlier trials with positive ranging between 80.9% and 100% 25,26 have been reported.…”
Section: Discussionsupporting
confidence: 90%
“…Although the majority of WT1 molecular investigations have revealed 100% positivity, 26 several research employing the IHC technique have discovered missing expression in a small number of astrocytomas. In their analysis of 73 astrocytomas, Mahzouni and Meghdadi 27 observed that 97.3% of the time, WT1 protein was expressed.…”
Section: Discussionmentioning
confidence: 99%